Evolução da cooperação entre antropóides virtuais: um modelo computacional baseado em agentes - Jakson Alves de Aquino (2008)
This thesis presents a theoretical investigation into the evolution of cooperation among virtual anthropoids. Arguments are advanced in favor of a greater formalization of theory in social sciences and of use of agent-based models as a complementary method for theoreticalinvestigation. Review of the extant literature on the evolution of cooperation includes an effort to identify shortcomings of the models found. Suggested as a means toward surmounting these deficiencies is a greater understanding of empirical data relevant to formulation of a theory of the evolution of cooperation, such as those data yielded by primatology in study of anthropoids and by paleoanthropology in study of vestigial inheritances from our extinct ancestors. From a basis in this literature arises a proposed model of the evolution of cooperationthis model tested in computer simulationwhich is more complex and more realistic than the models reviewed. Cooperation anticipated in elaboration of the model did not emerge in a generalized manner,notwithstanding the emergence of an elevated degree of cooperation between agents of opposite sex. The results obtained indicate that sexual reproduction, absent from the models submitted to review, is a variable highly relevant to this inquiry. The experiments also show a surprisingpropensity on the part of the agents toward non-retaliation, which propensity remains to be duly interpreted in theoretical terms.